Kendala Pendidikan Kewarganegaraan dalam membangun karakter peserta didik di dalam proses pembelajaran - Widiatmaka, Pipit (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
This study has the objective to discuss in depth about the obstacles experienced by Citizenship Education teacher in building the student’s character. This type of research is qualitative. Data collection method were literature study and observation. Data were analyzed using interactive data analysis. Civic Education is a lesson that must be given to students from elementary school to college, so it is not denied that Civic Education has a significant in building a good citizen. Basically, Civic Education teacher’s responsibility is huge, because the task is not only to build knowledge of civic (civic knowledge), but also to build the skills of civic (civic skills) and character (civic disposition). Up to now, the effort were not yet brought about a maximal result. The reasons were many such as cognitive-heavy, lack of teacher’s competence, had teaching the emphasis on civic knowledge, but not civic skills and dispositions.